Leonotis ocymifolia (Burm.f.) Iwarsson aerial parts aqueous extract mitigates cisplatin-induced nephrotoxicity via attenuation of inflammation, and DNA damage - Mufti, Afoua; Feriani, Anouar; Ouchari, Wafae; Mandour, Yasmine M.; Tlili, Nizar; Ibrahim, Mohammed Auwal; Mahmoud, Mona F.; Sobeh, Mansour (Frontiers in Pharmacology, 2023)
Herein, we explored the protective effect of Leonotis ocymifolia (Burm.f.) Iwarsson aerial parts extract (LO) against cisplatin (CP)-induced nephrotoxicity in rats and profiled their phytocontents. A total of 31 compounds belonging to organic and phenolic acids and their glycosides as well as flavonoids and their O-and C-glycosides were identified through LC-MS/MS. The DPPH and FRAP assays revealed that the extract had powerful antioxidant properties. The in vivo results demonstrated that administering LO extract for thirty days (40 and 80 mg/kg b.w.) significantly improved the altered renal injury markers via reducing creatinine (high dose only) and uric acid levels compared to the Cp-group. The deleterious action of cisplatin on renal oxidative stress markers (GSH, MDA, SOD, and CAT) were also restored by LO-pretreatment. The reduction of the inflammatory marker (IL-6), and inhibition of DNA fragmentation, highlighted the prophylactic action of LO in kidney tissue. Molecular docking followed by a 100 ns molecular dynamic simulation analyses revealed that, amongst the 31 identified compounds in LO, chlorogenic and caffeoylmalic acids had the most stable binding to IL-6. The nephroprotective effects were further confirmed by histopathological observations, which showed improvement in ultrastructural changes induced by cisplatin. The observed findings reinforce the conclusion that L. ocymifolia extract exerts nephroprotective properties, which could be related to its antioxidant and anti-inflammatory activities. Further studies are required to determine the therapeutic doses and the proper administration time.